Induction of Re-Differentiation of Passaged Rat Chondrocytes Using a Naturally Obtained Extracellular Matrix Microenvironment - Cha, Myung Hwa; Do, Sun Hee; Park, Ga Ram; Du, Ping; Han, Ki-Chul; Han, Dong Keun; Park, Kwideok (MARY ANN LIEBERT, INC, 2013)
Dedifferentiated human chondrocytes severely limit successful hyaline cartilage repair in clinical practice. The primary interest of this study is to evaluate the naturally obtained cell-derived matrix (CDM) as a physical microenvironment for chondrocyte re-differentiation. Once different cell types were cultured for 6 days and decellularized using detergents and enzymes, the fibroblast-derived matrix (FDM), preosteoblast-derived matrix (PDM), and chondrocyte-derived matrix (CHDM) were obtained. From scanning electron microscope observation, each CDM was found to resemble a fibrous mesh with self-assembled fibrils. Both the FDM and PDM showed a more compact matrix structure compared to the CHDM. For compositional analysis, sodium dodecyl sulfate-polyacrylamide gel electrophoresis displayed numerous matrix proteins, which were quite different from each CDM in quantity and type. Specific matrix components, such as fibronectin, type I collagen (Col I), and laminin, were detected using immunofluorescent staining. In addition, the water contact angle suggests that the FDM is more hydrophilic than the PDM or CHDM. The proliferation of rat primary chondrocytes growing on CDMs was better than those growing on a plastic coverslip (control) or gelatin. Meanwhile, synthesis of glycosaminoglycan (GAG) was more effective for passaged chondrocytes (P4) cultivated on CDMs, and the difference was significant compared to cells grown on the control or on gelatin. As for the gene expression of cartilage-specific markers, CDMs exhibited good chondrocyte re-differentiation with time: the dedifferentiating marker, Col I was restrained, whereas the ratio between Col II and Col I, and between aggrecan and Col I, as an indicator of re-differentiation, was greatly improved. In addition, immunofluorescence of Col II showed a very positive signal in chondrocytes cultivated for 2 weeks on the CDMs. In an additional study, when three-dimensional cell pellets made from either plate-grown or matrix-grown dedifferentiated chondrocytes (P5) were cultured for 4 weeks, the results of Safranin-O staining, immunohistochemistry of Col II, and total GAG assay suggested that matrix-grown cells were significantly better in the induction of chondrocyte re-differentiation, than those grown on the plate. This work suggests that the naturally occurring matrix, CDM, can provide a favorable surface texture for cell attachment, proliferation, and more importantly, a chondroinductive microenvironment for the re-differentiation of dedifferentiated chondrocytes.
Keywords: HUMAN ARTICULAR CHONDROCYTES; STEM-CELL DIFFERENTIATION; CULTURE-SYSTEM; REDIFFERENTIATION; DEDIFFERENTIATION; CARTILAGE; TISSUE; SUBPOPULATIONS